DAMPs in Unilateral Ureteral Obstruction - Wyczanska, Maja; Lange-Sperandio, Bärbel (Frontiers in Immunology, 2020)
Damage-associated molecular patterns (DAMPs) are released from tubular and interstitial cells in the 10 kidney after unilateral ureteral obstruction (UUO). DAMPs are recognized by pattern recognition 11 receptors (PRRs), which mediate the initiation of an immune response and the release of inflammatory 12 cytokines. The animal model of UUO is used for various purposes. UUO in adult mice serves as a 13 model for accelerated renal fibrosis, which is a hallmark of progressive renal disease. UUO in adult 14 mice enables to study cell death, inflammation, and extracellular matrix deposition in the kidney. 15 Neonatal UUO is a model for congenital obstructive nephropathies. It studies inflammation, apoptosis, 16 and interstitial fibrosis in the neonatal kidney, when nephrogenesis is still ongoing. Following UUO, 17 several DAMPs as well as DAMP receptors are upregulated. In adult UUO, soluble uric acid is 18 upregulated and activates the NOD-like receptor family, pyrin domain containing-3 (NLRP3) 19 inflammasome, which promotes fibrosis, apoptosis, and reactive oxygen species (ROS) injury. Further 20 DAMPS associated with UUO are uromodulin, members of the IL-1 family, and necrotic cell DNA, 21 all of which promote sterile inflammation. In neonatal UUO, the receptor for advanced glycation 22 endproducts (RAGE) is highly upregulated. RAGE is a ligand for several DAMPS, including high 23 mobility group box 1 (HMGB1) and S100 proteins, which play an important role in renal fibrosis. 24 Additionally, necroptosis is an important mechanism of cell death, besides apoptosis, in neonatal UUO. 25 It is highly inflammatory due to release of cytokines and specific DAMPs. The release and recognition 26 of DAMPs initiate sterile inflammation, which makes them good candidates to develop and improve 27 diagnostic and therapeutic strategies in renal fibrosis and congenital obstructive nephropathies.